Respuesta :

[tex]\bf 5x^2~~-~~(2x-3)^2\implies 5x^2~~-~~(2x-3)(2x-3) \\\\\\ 5x^2~~-~~(4x^2-12x+9)\implies 5x^2~~-4x^2+12x-9 \\\\\\ x^2+12x-9[/tex]

The solution of the given expression will be -x ² -12x  +  9.

What is an expression?

Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division

Given expressions are:-

=   (  2x -  3  )²  -   5x²

=   (  4x² +  12x  +  9  -  5x²  )

=   (  -x²  +  12x  +  9  )

Therefore the solution of the given expression will be -x ² -12x  +  9.

To know more about Expression follow

https://brainly.com/question/723406

#SPJ2